Endoscopic findings and emerging complications after ingestion of corrosive substances - Simonovska, Natasha; Velikj stefanovska, Vesna; Babulovska, Aleksandra; Pereska, Zanina; Kostadinoski, Kristin; Naumoski, Kiril (GUARANT International spol. s r.o., 2021)
Aim: To evaluate the most commonly ingested corrosive substance, endoscopic findings, complications and the final outcome of caustic intake. Methods: This cross sectional study covered 220 inpatient participants during a three years period (2017- 2019). Data from the National patient electronic system “My term” and from the “Poisoning information center” at University Clinic of Toxicology, Skopje were used. Demographic characteristics, type of corrosive substance, endoscopic findings – Kikendall classification, emerging complications, fatal outcome, and hospitalization were analyzed. Results: Out of 220 inpatient cases with corrosive substance intake, there were acids 60% (n=132), bases 8.6% (n=19), bleaches 14.5% (n=32) and other household products 16.8% (n=37). Patients which took acids/bases were significantly older compared to bleaches/other (p=0.0009). Hospitalization was significantly longer in base and acid ingestion compared to bleaches and other (p=0.0005). Upper gastrointestinal endoscopy was declined by 10% (n= 22) and 10% (n=22) of patients were with fatal outcome. The most severe endoscopy findings were in acid and base ingestion. Esophagus findings in acids -grade I (1.92%), grade IIA (50%), grade IIB (27%) and grade III (21.1%), in bases – grade IIA (7.2%), grade IIB (57.1%) and grade III (35.7%); Stomach findings in acids-grade I (2.9%), grade IIA (29.8%), grade IIB (37.5%), grade III (29.8%), in bases-grade IIA (13.4%), grade IIB (33.4%), grade III (53.2%); Duodenum findings in acids-grade I (62.5%), grade IIA (23.1%), grade IIB (14.4%), in bases-grade IIA (26.7%), grade IIB (40%), grade III (33.3%). In 22.2% (n=39) of cases were registered complications (strictures): esophagus 43.6% (n=17), stomach 25.7% (n=10), on both organs 30.8% (n=12). Conclusion: Corrosive substances result in serious injuries to the mucosa of the gastrointestinal tract, which are confirmed by endoscopic findings. These conditions are often accompanied by complications such as strictures and can lead to fatal outcomes as well.
Keywords: corrosive substance; Kikendall classification; strictures; hospitalization